Análise do balanço de energia entre a interface atmosfera-gelo-água sobre o Mar de Weddell - Brito Neto, Francisco Agustinho de (Brasil, 2017)
The polar regions play a crucial role in the climate of the planet, as they constitute true energy sinks. The Antarctic continent presents physical and geographical characteristics that provide the generation of adverse weather conditions, having another important attribute the great interannual variability of the sea ice. This study has as one of the objectives to study and evaluate the behavior of marine ice conditions at fixed points in the sea of Weddell, as well as the energy flows in surface and temperature of the air, using a dynamic model punctual. The area of study corresponds to the sea of Weddell situated in the southern part of the Atlantic Ocean, between the latitudes 83 ° 10 ' South at 55 ° 00 ' South and longitudes 84 ° 00 ' West at 10 ° 00 ' East. This area covers approximately 3.4 million km² corresponding to approximately the size of Weddell. Another objective is to characterize the surface climatic conditions in the region. For this use daily data of atmospheric pressure on surface, speed and direction of the wind, in addition to the air temperature at 2 meters, from 6 meteorological stations of the Argentine Antarctic Institute located along the Continental edge that comprises the sea of Weddell. In this way, a study of the extreme conditions at wind speed was carried out, with data of reanalysis of the Era-Interim, for the winds of the region and the south, pressure at the average sea level and geopotential height. For the initial conditions that feed the time model of marine ice, data were used of the daily energy flows and radiation from the reanalysis of NCEP/NCAR. The study period comprises January from 1979 to December 2015. As for the characterization of the weather conditions on the sea of Weddell it was observed that when there are extreme events in the region, these were associated with transient extratropical cyclones. It also has an impact on the increase in temperature in most stations due to the advection of temperature from smaller latitudes. The simulations with the punctual ...